A general variable neighbourhood search for the commodity constrained split delivery vehicle routing problem. Issue 2 (7th June 2023) - Cheikh, Mohamed; Loukil, Taicir Moalla
The commodity constrained split delivery vehicle routing problem (C-SDVRP) is a relaxed version of the classical VRP. This problem emanates where customers request several commodities that can be delivered separately using a set of vehicles. With limited capacity, these vehicles can convey any mixed commodities set. More than one vehicle may visit one customer, and in each visit, each product must be delivered in its entirety. The objective is to minimise the total cost of the vehicle routes. To solve the C-SDVRP, we propose a general variable neighbourhood search (GVNS) that uses a random variable neighbourhood descent (RVND), in which we explore five neighbourhood structures. Computational experiments on large-sized instances show that the proposed approach finds several new best-known solutions, together with some improvement on the number of used vehicles. The results demonstrate that GVNS has a fast convergence rate and high computational accuracy.